Effect of Wrist-Ankle Acupuncture Point Stimulation on Preventing Postoperative Nausea and Vomiting in Female Patients Undergoing Orthopedic Surgery - Zhang, Zhenzhen; Liu, Qingge; Chen, Rui; Tian, Yamin; Wang, Chaoping; Zhang, Di; Wu, Songmei (Journal of perianesthesia nursing, 2025)
To observe the clinical effects of a preventive nursing intervention involving wrist-ankle acupuncture point stimulation on postoperative nausea and vomiting among female patients who underwent orthopedic surgery. Randomized control trial. Female patients who underwent lumbar open reduction, bone graft fusion, or internal fixation surgery in the operating room of a tertiary first-class hospital in Henan Province from October 2022 to June 2023 were selected as the research subjects. The patients were randomly divided into an experimental group and a control group via the random number table method. The experimental group (n = 38) received a wrist and ankle acupuncture point stimulation nursing intervention, whereas the control group (n = 38) received routine perioperative care. The serum concentrations of 5-hydroxytryptamine (5-HT) and gastrin, opioid usage, postoperative complications, and patient satisfaction were compared between the two groups. No statistically significant difference (P > .05) was found between the two groups in terms of general information, such as age, weight, surgical time, opioid use, or preintervention gastrointestinal hormone levels. The serum concentrations of 5-HT and gastrin at T1 (before skin incision), T2 (after surgery), and T3 (24 hours after surgery) were significantly lower in the experimental group than in the control group (P < .05). The satisfaction of patients in the experimental group was significantly higher than that in the control group (P < .05). Wrist-ankle acupuncture point stimulation can reduce the incidence of postoperative nausea and vomiting in female patients undergoing orthopedic surgery, reduce the serum concentrations of 5-HT and gastrin, reduce complications, and improve patient satisfaction while not impacting analgesic effects.